Search for Bs 0 - Bs 0 oscillations and a measurement of Bd 0 - Bd 0 oscillations using events with an inclusively reconstructed vertex: The Delphi collaboration - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2003)
Neutral B meson oscillations in the Bs0 - Bs0 and Bd0 - Bd0 systems were studied using a sample of about 4.0 million hadronic Z decays recorded by the DELPHI detector between 1992 and 2000. Events with a high transverse momentum lepton were removed and a sample of 770 k events with an inclusively reconstructed vertex was selected. The mass difference between the two physical states in the Bd0 - Bs0 system was measured to be: Δmd = (0.531 = 0.025(stat.) ± 0.007(syst.))ps-1. The following limit on the width difference of these states was also obtained: |ΔΓBd|/ΓBd < 0.18 at 95% CL. As no evidence for Bs0 - Bs0 oscillations was found, a limit on the mass difference of the two physical states was given: Δms > 5.0 ps-1 at 95% CL. The corresponding sensitivity of this analysis is equal to 6.6 ps-1.